Lighting up the Andes [LED lamps]. - Fairley, P.
This work relates how a pair of 62-year olds from Canmore, Alberta in Canada, have made it their mission to free remote communities from reliance on costly kerosene lighting. Anthony and Faith Harckham have developed a simple LED lamp which consumes only 1 watt and produces 30 lumens in a focused beam about as bright as the light of a 20 W incandescent bulb. The couple devised a small volunteer operation that blends tourism and charity. Called Luxtreks, the operation has installed lighting systems in more than 700 rural homes in Bolivia, Guatemala, Peru and Pakistan without taking a dime of government money. The trekers travel with the couple and personally deliver their gift by installing the LED lamps themselves. At the same time, the trip provides trekkers a unique, in situ experience about as culturally distant from their daily lives as they could have imagined.
Keywords: LED lamp; Luxtreks; Electrical installation process; Solar panels